2018
DOI: 10.1155/2018/3717328
|View full text |Cite
|
Sign up to set email alerts
|

Combined Donepezil and Ethanolic Extract of Propolis Improved Memory Better Than Donepezil and Propolis Monotherapy in Wild Type Drosophila melanogaster

Abstract: Background Donepezil is the most common drug used in the treatment of disorders associated with memory loss, especially that in Alzheimer's disease. Healthy individuals however have continued to use it as a memory enhancer. This study was aimed at evaluating the combined therapy of donepezil and propolis on cognition in Drosophila melanogaster. Method. Drosophila melanogaster flies were divided into five groups and fed with the different treatment doses of ethanolic extract of propolis and donepezil as follows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In this way, several drugs and natural extracts are tested for this purpose. Among them are omega 3, turmeric, and propolis (Ayikobua et al, 2018;de Oliveira Souza et al, 2019;Mishra & Palanivelu, 2008). Our study correlated acetylsalicylic acid, commonly known as aspirin, to a neuroprotective effect on the brain of D. melanogaster.…”
Section: Discussionmentioning
confidence: 74%
“…In this way, several drugs and natural extracts are tested for this purpose. Among them are omega 3, turmeric, and propolis (Ayikobua et al, 2018;de Oliveira Souza et al, 2019;Mishra & Palanivelu, 2008). Our study correlated acetylsalicylic acid, commonly known as aspirin, to a neuroprotective effect on the brain of D. melanogaster.…”
Section: Discussionmentioning
confidence: 74%
“…This study has shown that acute exposure of D. melanogaster to AlCl 3 at a concentration as low as 40 mM is capable of significantly decreasing their survival, locomotors performance, and aversive phototaxic suppression (APS). Both the locomotor performance and APS are validly used in drosophila to access neuromuscular functions, aging, learning, and memory (Ali, Escala, Ruan, & Zhai, 2011; Ayikobua et al, 2018). Therefore, our findings further confirms the potent toxicity of Al in D. melanogaster, especially to the fly's neuronal system.…”
Section: Discussionmentioning
confidence: 99%
“… Ayikobua et al (2018) investigated the combined effect of donepezil and ethanolic extract of propolis (source not specified) in wild-type Drosophila melanogaster ( n = 10 each group) ( Ayikobua, Semuyaba, 2018 ). Their results demonstrated that 10 ml of donepezil (0.001 M) combined with 50 mg propolis in food exhibited a time-dependent improvement trend in the short- and long-term memory for 30 days.…”
Section: Pharmacodynamic Interactionsmentioning
confidence: 99%